PENERAPAN MODEL KOOPERATIF TPS DISERTAI PICTURE AND PICTURE MATERI ORGANISASI KEHIDUPAN KELAS VII SMP - Harmistri, Yolanda Olivia; Ningsih, Kurnia; Wahyuni, Eko Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aims to know the influence of think pair share (TPS) cooperative learning model with picture and picture on the student learning outcomes in material of life organization in the Seventh Grade of Â SMP Muhammadiyah 1 Pontianak. This research was quasi experimental design with nonequivalent control group design. The sampling technique was used saturation sampling technique. Research samples were class VII C as the experimental class with 28 students and VII B as the control class with 28 students. The instrument was used the multiple choice test with a total of 20 questions. The average student learning outcome in the experimental class was 16,04, while in the control class was 13,86. The results of the U Mann-Whitney test analysis showed that Zcount<-Ztable that is Â -4,27 Ë‚ -1,96, it was meant there significant difference between students that taught by using TPS cooperative learning model with picture and picture and conventional learning model. The effect size value obtained was 1,03 with high category, having an effect of 34,85%.Keywords: TPS cooperative learning model with picture and picture, learning outcome